An Experimental Study on the Impact of Collaborative and Active Learning on Vocational Students' Learning Achievement and Self-Motivation - Li, Ruijuan; Srikhao, Sarit; Jantharajit, Nirat (GIST – Education and Learning Research Journal, 2024)
The study examines a blended instructional approach combining collaborative and active learning to improve vocational students' learning achievement and self-motivation. An experimental design was utilized, dividing vocational students into control and experiment groups. The experiment group participated in a one-month collaborative and active learning intervention, while the control group received traditional instruction. The experiment group achieved significant gains in academic achievement, with pre-test and post-test means rising from 79.63 to 86.15 (t=19.72, p<0.05) and self-motivation scores increasing from 37.82 to 42.74 (t=19.71, p<0.05). In contrast, the control group exhibited lower post-test scores in both academic achievement (mean=80.16, t=3.67, p<0.05) and self-motivation (mean=38.4, t=5.31, p<0.05). These results indicate that integrating collaborative and active learning strategies significantly impacts learning achievement and self-motivation in vocational education. This suggests that this instructional approach is highly effective in improving student outcomes.